Implementasi Metode Pembiasaan Menghafal Doa Harian pada Anak Usia 5-6 Tahun - Nur Nisai Muslihah; Akbari Akbari (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini, Fakultas Tarbiyah dan Keguruan, Universitas Islam Bandung., 2025)
This study aims to describe the implementation of daily prayer memorization habituation methods, teachers’ strategies, the role of parents, as well as supporting and inhibiting factors at TKIT Al-Qudwah Musirawas. The research employed a descriptive qualitative approach with triangulation techniques through observations, interviews, and documentation involving the school principal, teachers, parents, and children aged 5–6 years. The findings indicate that prayer habituation is implemented in a structured manner through teachers’ role modeling, daily routines, murojaah (repetition), and the integration of Islamic thematic learning. Supporting facilities such as guidebooks, mutaba’ah records, and visual media strengthen the learning process. Supporting factors include teachers’ commitment and a religious school culture, while the main inhibiting factor is the lack of parental involvement at home. The habituation of daily prayers is effective in fostering children’s discipline, independence, and spiritual awareness.